The Perceived Impact of Online Course Design on the Persistence of Students at Historically Black Colleges and Universities - Stevenson, Alana N.; Brown, Walter A. (Advances in Social Sciences Research Journal, 2023)
This research study aimed to investigate the influence of online course design on the persistence of undergraduate students at Historically Black Colleges and Universities (HBCUs). By examining the concept of persistence, the study aimed to enhance understanding of how integrated online learning materials can promote student engagement, academic assimilation, and social acceptance. The study considered the impact of the COVID-19 pandemic on online education and sought to contribute to discussions on online course design effectiveness. The study was conducted at two HBCUs in the southern region of the United States. A qualitative research method was employed, utilizing purposeful criterion-based sampling. Seventeen undergraduate students who had enrolled in fully-online courses participated in semi-structured interviews, which were transcribed and analyzed using open, axial, and selective coding techniques. The findings revealed several themes related to student persistence in online courses. Participants expressed a preference for asynchronous learning, highlighting the flexibility it offered. Student-instructor interaction was identified as vital, emphasizing the importance of regular engagement, personalized guidance, and timely feedback. The value of multimedia resources and engagement with classmates was recognized, with participants valuing diverse materials and interactions that enhanced their understanding and motivation. Community-building activities, such as online discussions and group projects, were found to foster a sense of belonging and encourage active participation. These findings provide insights for HBCUs and higher education institutions to enhance online course design and support mechanisms for student persistence. The study underscores the significance of teacher presence, interactive learning environments, and institutional support for online educators and contributes to the advancement of online education and promotes successful student outcomes within the context of HBCUs.